Post-translational changes in Phialophora verrucosa via lysine lactylation during prolonged presence in a patient with a CARD9-related immune disorder - Song, Yinggai; Liu, Xiao; Stielow, J. Benjamin; de Hoog, Sybren; Li, Ruoyu (Frontiers in Immunology, 2022)
CARD9-related inherited immune disorders are a major risk factor for chronic disseminated fungal infection. In addition to pathogens of Candida and dermatophytes, the environmental opportunists of the black yeast-like fungi are relatively frequent in this patient cohort. Particularly the genus Phialophora is overrepresented. We investigated two isolates of a strain of P. verrucosa residing in a CARD9 patient, sampled with a period of ten years apart. Genomes, melanization and antifungal susceptibility of progenitor and derived strains were compared, and potential adaptation to the host habitat was investigated with proteomic techniques using post-translational modification as a proxy. Global lactylation analysis was performed using high accuracy nano-LC-MS/MS in combination with enrichment of lactylated peptides from digested cell lysates, and subsequent peptide identification. The genome of the derived isolate had accumulated 6945 SNPs, of which 31 were detected in CDS. A large number of identified proteins were significantly enriched, e.g. in melanin biosynthesis. A total of 636 lactylation sites on 420 lactylated proteins were identified, which contained in 26 types of modification motifs. Lysine lactylation (Kla) was found in 23 constituent proteins of the ribosome, indicating an impact of Kla in protein synthesis. Twelve lactylated proteins participated in pathogenicity. A protein-protein interaction (PPI) network analysis suggested that protein lactylations are widely distributed influencing various biological processes. Our findings reveal widespread roles for lysine lactylation in regulating metabolism and melanin biosynthesis in black fungi. Several large rearrangements and inversions were observed in the genome, but genomic changes could not be linked to adaptation or to known clinically relevant properties of progenitor to derived isolate; in vitro antifungal susceptibility had largely remained unaltered.